Hipomineralización incisivo Y molar: diagnóstico diferencial - Souza, Juliana Feltrin [UNESP]; Jeremias, Fabiano [UNESP]; Silva, Cristiane Maria da Costa [UNESP]; Zuanon, Angela Cristina Cilense [UNESP]; Santos-Pinto, Lourdes Aparecida Martins dos [UNESP]; Cordeiro, Rita De Cássia Loiola [UNESP] (My University, 2011)
Hypomineralized first molar often in combination with hypomineralized incisors (MIH - molar incisor hypomineralization) is a common finding in everyday practice. In this condition, hypomineralized dental enamel is fragile and soft, and it can break easily leading to an exposed dentin, and causing dental sensitivity and progression of caries lesions. The prevalence of MIH range from 3.6 to 25% in North of Europe that consider this condition a public health problem. No conclusive information was reported about the etiologic factors of MIH, however, systemic causes seem to be of importance. Several aetiological factors are mentioned as the cause of this condition and they are frequently associated with complications during pregnancy and childhood diseases during the first three years of life. MIH is frequently misinterpreted as fluorosis, hypoplasia or amelogénesis imperfect, however, this condition presents defined clinical aspects that can distinct it from the other defects.

La hipomineralización de primeros molares frecuentemente es acompañada con una hipomineralización de incisivos (HIM - Hipomineralización Incisivo y Molar) esto es comúnmente encontrado en la práctica clínica. El esmalte hipomineralizado es frágil, puede fracturarse y dejar expuesta la dentina, causando sensibilidad dental y aumento del riesgo de caries. La prevalencia de HIM varía de 3,6 a 25% en el norte de Europa, siendo considerada un problema de salud pública. En cuanto a los factores etiológicos los datos no son definidos, por lo cual causas sistémicas parecen importantes. Los posibles factores etiológicos de este cambio son a menudo relacionados con problemas en el embarazo y enfermedades de la infancia en los tres primeros años de vida. El HIM es frecuentemente confundido con otros defectos del esmalte como amelogénesis imperfecta, la fluorosis y la hipoplasia, sin embargo, detalles sobre las características clínicas de esta condición pueden diferenciarlo de otros defectos del esmalte.
Keywords: Hypomineralization; Incisors; Molars; Differential diagnosis; Amelogénesis imperfect; Fluorosis dental; Hipomineralización de los dientes; Incisivos; Molares; Diagnóstico diferencial; Amelogénesis imperfecta; Fluorosis dental